Development of Urban Centres in Kenya: the Case of Keroka Town (1905-2018) - Mbeta, Richard Nyakebondo (JOOUST, 2022)
The emergence and development of urban centres has been a major topic of study across the globe as urbanization continues to engulf most open and suitable spaces. The historical emergence of some major towns in Kenya has not been left behind. However, smaller towns which are equally important in understanding the complexities of urbanization in a nation still call for investigation. Keroka town having started as a social and cultural centre in the colonial period has become a rapidly growing urban centre. Therefore there need to investigate the emergence and development of Keroka Urban Centre as a case study to understand the process of urbanization in Kenya’s rural set-up. The objectives used to realize this were; i) to examine the emergence and growth of Keroka Urban Centre during the colonial period from 1905 to 1963, ii) to analyze the development of Keroka in the post colonial period of 1963 to 2018, and iii) to establish the development challenges and impact of Keroka town on its residents and environs. The study adopted village magnet and ribbon models of urbanization theories to explain and interpret the data, as well as used historical research design to guide the study. A sample size of 46 informants was interviewed using purposive and snowball sampling methods. Qualitative data was collected by using interview schedules, focus group discussion guides, observation, and archival records for primary data, as research instruments. Quantitative data was obtained from secondary data sources. Qualitative data was analyzed using thematic data analysis method while quantitative data was analyzed using simple statistical methods such as means presented in tables and graphs. The findings indicated that Keroka emerged in the colonial period as a social and cultural centre and continued to grow due to the economic and administrative activities of the colonial government. It developed over time due to population increase, road network, missionary work, introduction of western education and cash crops, increased business opportunities and security among other factors. The challenges the town faced included inadequate social amenities such as hospitals, schools, modern sporting grounds, and lack of major departmental offices to serve the residents. There was also congestion and rise of slums, lack of designated market space, and environmental degradation, boundary and resource conflicts among others.The study recommended that there should be expansion of other offices, such as, agricultural research, gender affairs, heritage and sports, as well as industrialization in order to bring more services closer to the residents and the surrounding areas. Further, Keroka Cultural centre should be enlarged to enhance Gusii cultural activities. There should also be the enforcement of adequate legal framework in land development and proper urban centre planning.
Keywords: Development; Urban Centres